Action and Object Naming in Physiological Aging: An rTMS Study - Cotelli, Maria; Manenti, Rosa; Rosini, Sandra; Calabria, Marco; Brambilla, Michela; BISIACCHI, PATRIZIA; Zanetti, Orazio; Miniussi, Carlo (Frontiers in Aging Neuroscience, 2010)
Word-retrieval difficulties commonly occur in healthy aging. Recent studies report an improved ability to name pictures after the administration of high-frequency repetitive transcranial magnetic stimulation (rTMS) in healthy younger adults and in patients with neurological disease. The aim of this study was to assess the effect of high-frequency rTMS applied to the dorsolateral prefrontal cortex (DLPFC) on picture naming in healthy older adults. High-frequency rTMS was applied to the left and right DLPFC during object and action naming in thirteen healthy older adults. The naming latency for actions was shortened after stimulation of the left and right DLPFC compared to application of the sham stimulation. Stimulation was not observed to have any effect on correctness of naming. Our data demonstrate the involvement of the left and right DLPFC in a sample of healthy aging subjects during an action-naming task. The bilateral involvement of the DLPFC in these participants is discussed together with data on younger adults and on Alzheimer’s patients.